Monte Carlo simulation on dielectric relaxation and dipole cluster state in relaxor ferroelectrics - 朱琛 刘俊明 (Chinese physics B, 2010)
The Ginzburg-Landau theory on ferroelectrics with random field induced by dipole defects is studied by using Monte Carlo simulation, in order to investigate the dipole configuration and the dielectric relaxation of relaxor ferro-electrics. With the increase of random field, the dipole configuration evolves from the long-range ferroelectric order into the coexistence of short-range dipole-clusters and less polarized matrix. The dipole-cluster phase above the transition temperature and superparaelectric fluctuations far below this temperature are identified for the relaxor ferroelectrics. We investigate the frequency dispersion and the time-domain spectrum of the dielectric relaxation, demonstrating the Vogel-Fulcher relationship and the multi-peaked time-domain distribution of the dielectric relaxation.